"There Needs to be a Place in Society for Madness": The Psychiatric Survivor Movement and New Directions in Mental Health Care. (October 2014) - Adame, Alexandra L.
The psychiatric survivor movement is an international coalition of grassroots organizations that work for human rights in the mental health system. Previous research has examined how the survivor movement has critiqued and envisioned alternatives to traditional mental health services. The current study focused on a unique group of individuals who identify as both psychiatric survivors and work as therapists in the mental health system. I interviewed several people with this dual-identity to better understand their approaches toward activism and psychotherapy. This article focuses on one of the survivor-therapist's experiences, and I explore the broader clinical implications for both survivors and mental health professionals and next steps for developing viable alternatives to the traditional system.